2020
DOI: 10.1016/j.neurobiolaging.2019.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of age-related microstructural changes in locus coeruleus and substantia nigra pars compacta

Abstract: Locus coeruleus (LC) and substantia nigra pars compacta (SNpc) degrade with normal aging, but not much is known regarding how these changes manifest in MRI images, or whether these markers predict aspects of cognition. Here, we use high-resolution diffusion-weighted MRI to investigate microstructural and compositional changes in LC and SNpc in young and aged cohorts, as well as their relationship with cognition. In LC, the older cohort exhibited a significant reduction in mean and radial diffusivity, but a sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 67 publications
(96 reference statements)
7
61
2
Order By: Relevance
“…The present result accords well with our prior work despite the age difference between the two control cohorts, and this agreement may suggest that iron deposition in the SNpc derived from NM-MRI is not dependent on age in normal subjects and is primarily due to PD. Additionally, SNpc R 2 * values in the control group are in line with those published in an earlier study examining age-related iron deposition in SNpc ( Langley et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…The present result accords well with our prior work despite the age difference between the two control cohorts, and this agreement may suggest that iron deposition in the SNpc derived from NM-MRI is not dependent on age in normal subjects and is primarily due to PD. Additionally, SNpc R 2 * values in the control group are in line with those published in an earlier study examining age-related iron deposition in SNpc ( Langley et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…A growing body of literature has suggested that the LC-NE system plays a role in cognition in later life, with recent studies linking in vivo estimates of LC neuronal integrity to cognitive outcomes in older adults (Clewett et al, 2016;Dahl et al, 2019;Hämmerer et al, 2018;Langley et al, 2020). In this study, we aimed to build upon this literature to determine whether LC neuronal integrity predicted cortical thickness, one aspect of brain structure and a documented brain indicator of cognitive ability in older adulthood (Fjell et al, 2006;Lee et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Measures of mean, radial, and axial diffusivity would help clarify precise changes to LC axons over the course of disease. In healthy participants, aging appears to increase fractional anisotropy and lowers both mean and radial diffusivity of the LC ( Langley et al, 2020 ). The authors propose decreased LC axon diameter underlie these results, but follow up studies should directly test this hypothesis.…”
Section: Human Studiesmentioning
confidence: 99%